3D model of a Monolithic Honeycomb Adsorber for Electric Swing Adsorption for Carbon Dioxide Capture - Ječmenica Dučić, Marija; Đukić, Ivana; Nikačević, Nikola; Petkovska, Menka (Journal of Engineering & Processing Management, 2020)
The goal of this work was to develop a 3D model of Electric Swing Adsorption process for carbon dioxide capture from effluent gasses from power plants. Detailed 3D model of the composite honeycomb monolithic adsorber was developed for a single monolith channel and can be used to simulate and represent different physical properties: velocity, concentration and temperature. The advantage of this model is the fact that all physical properties and results can be presented visually in the 3D domain. COMSOL Multiphysics software was used for solving partial differential equations and simulations of adsorption and electrothermal desorption processes. Some simulation results are presented in this work. The results obtained from 3D simulations will be used for the adsorber model reduction to the 1D model which will be used for modeling and optimization of the whole ESA cycle due to its simplicity and computational demands. Simulation and optimization runs based on the 1D model will be performed in g-Proms software.